Pengembangan Media Pembelajaran Gamifikasi Berbasis Web Untuk Materi Input-Process-Output Dan Arsitektur Komputer Von Neumann Pada Informatika Kelas X - Nur Kholis Wakhid; Ramadhan Cakra Wibawa (CV. SINAR HOWUHOWU, 2026)
Learning Input-Process-Output (IPO) and Von Neumann computer architecture is often challenging for tenth-grade students due to its abstract nature. This study aimed to develop a web-based gamified learning media for Informatics Grade X using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The media, named ArchiLogic, integrates gamification elements such as points, levels, leaderboards, and problem-based learning missions. Feasibility was assessed through expert validation: media experts gave a score of 90% and learning experts gave 92.14%, both categorized as